Pharmacological Importance of Sage and Oregano - Nida, Tabassum Khan (Journal of Advanced Pharmaceutical Science And Technology, 2020)
Sage and Oregano, both are well-known culinary herbs with potential medicinal uses. Sage is mostly used to cease wounds bleeding, treating sores, swelling, cough and ulcers back in the first century and was called as the fertility drug since it reduces excessive bleeding during menstruation. On the other hand Oregano was found to be effective in treating stomach discomforts, bacterial/fungal infection, inflammatory bowel disease etc. Therefore due to their therapeutic and native applications, Sage and Oregano is of high economic worth.
Keywords: Sage; Triterpenoids; Oregano; Ulcers; Gingivitis; Inflammatory bowel disease